A Foresight Study on the Adoption of Robotic Surgery in Malaysia - Siti Nuranisa Mohd Shahrol,; Siti Aisyah Salim, (Research in Management of Technology and Business, 2024)
Artificial intelligence (AI) has simply transformed the production of science fiction into a well-known phenomenon that has begun to diffuse in our daily lives. The application of robot has touched a wide range of industries, including production, services, research, and medical. Robotic surgery, also known as smart surgical tools, can assist in doing surgery on a single human being with greater efficacy, less injury, greater safety, and greater precision than a surgeon. Robotic surgical procedures can sometimes be complicated and sometimes simple. Moreover, the ethical issues and the successfulness of robotic surgery are still in the development phase since there are many issues and challenges in developing the robotic surgery. Other than that, the discussion on the adoption and the practicality of robotic surgery technology is still lacking in the context of Malaysia. Therefore, this study is being conducted to identify the key drivers of the robotic surgery adoption and determine the future trend of robotic surgery in Malaysia. In this research, the mixed method, which is both a qualitative and quantitative approach is used. The quantitative study is conducted by distributing the questionnaire to the surgeon in Malaysia. Ten merged key drivers and issues had been identified from the STEEPV analysis. A STEEPV analysis is employed as a foresight methodology. Next, impact-uncertainty analysis also been used to identify the future trend of robotic surgery. The response rate of these study is 65%. This study determines that improved surgical efficiency as well as ergonomic and user-friendly designs had the highest impact and uncertainty. Then, these top two drivers have been used in generating the scenario analysis which gives an overview of four alternative possibilities. The four scenarios were new medical norms, not interested in change, enhanced surgeons experience but decreased surgical output and also unsatisfactory technology.